A STUDY OF SINGLE ACCOUNT ON ACCOUTING FIRMS IN NAKHON SI THAMMARAT PROVINCE - SUTJASEN, ARTHIT; KLAEWTANONG, ARPORN; TEHLAH, AREE (วารสารวิชาการวิทยาลัยสันตพล, 2021)
Thailand has its own single Thai Financial Reporting Standards for the Publicly Accountable Entities (TFRSs for PAEs). The fair value concept is mainly used in the preparation of financial reports that was beneficial to SMEs. To sustainably develop the tax base, therefore, the government needs to promote and support the SMEs’ entrepreneurs for doing single accounting that is consistent with actual condition of entities. It will also help increase competitiveness in the ASEAN market. This study aimed to investigate the impact of single account on accounting firms, and to investigate the problems and obstacles of single account on accounting firms by collecting data from total 21 accounting entrepreneurs in Nakhon Si Thammarat Province using a questionnaire, and analyzing data using statistical analysis consisted of percentage, arithmetic average, and standard deviation. From the study of impact of single account on accounting firms, it was found that accounting firms were overall affected from single account at a moderate level. Impact of single account on accounting firms on overall providing the accounting service was at a moderate level, Impact of single account on accounting firms on overall accounting operation was at a high level, and on the overall process of follow-up and correction was at a high level. For other problems and obstacles of accounting entrepreneurs on single account, it was found that small accounting firms without updating TFRS law would have a problem of correct financial statement preparation because of updating shall be meet TFRS and work sheet.